Next-Generation Nanocarriers for Skin Cancer Therapy via Transdermal Delivery - Bhushan Rane; Nandini Mhatre; Ashish Jain (Nano Biomedicine and Engineering)
The global burden of cancer, a progressive disease with complex etiology, continues to rise. With an estimated 1.5 million new diagnoses each year, including nearly 350 000 cases of highly aggressive melanoma, the need for improved therapeutic strategies is paramount. The World Health Organization (WHO) and the International Labour Organization have established a clear link between occupational exposure to solar ultraviolet radiation (UVR) and increased risk of non-melanoma skin cancer (NMSC). While age, skin tone, and cumulative UVR exposure are recognized risk factors, current treatment modalities, including chemotherapy and surgery, often exhibit limited efficacy and significant side effects. This underscores the urgent need for novel therapeutic approaches that enable targeted drug delivery, enhanced tumor penetration, and reduced systemic toxicity. Transferosomes-based drug delivery systems have emerged as a promising avenue for achieving these goals, with vesicular systems offering a particularly attractive strategy for transdermal skin cancer therapy. This review focuses on transferosomes and transethosomes as such vesicular systems, highlighting recent advances in their application for targeted skin cancer treatment.